The role of pre-legislative scrutiny in complex law reform - the case of LASPO and its consequences for family justice - J Angelo Berbotto (IALS Student Law Review, 2019)
This paper considers the contribution of pre-legislative scrutiny to achieving quality legislation by analysing the Legal Aid, Sentencing and Punishment of Offenders Act 2012 (LASPO) in respect of access to legal aid in Private Family Law matters.  The article seeks to explain why pre-legislative scrutiny was not used in relation to the Bill and the red flags throughout the consideration of the Bill by Parliament.  It tracks the monitoring of LASPO once in force and how certain assumptions made by the Government were not accurate.   The article suggests that not using pre-legislative scrutiny in respect of LASPO was a missed opportunity.  Furthermore, it goes on to suggest that there should be better safeguards to ensure that pre-legislative scrutiny should be routinely used in respect of Bills that have far-reaching implications for individuals as, at the moment, it is up to the Government to decide what Bills are provided for pre-legislative scrutiny before their formal introduction into Parliament.